Fresno County Legal Services at 906 N Street - Watkins, Howard::::::::: (1978)
Ruben Lucero, ?, Janie Munoz, Jan Pearson, Ysidro Macias, Pat Sigala; Elaine Harris, Aggie Rose, Bob Higgins, ?, Dave Brodie, Catalina Peralta, Howard Watkins, Virginia Salmeron, Mary Ludy, Charles Kahill, Jan Pearson, Alice Gutierrez, , William Leifer, Gloria Escalante